In situ synthesis and unidirectional insertion of membrane proteins in liposome-immobilized silica stationary phase for rapid preparation of microaffinity chromatography - Yanqiu Gu; Rong Wang; Panpan Chen; Shengnan Li; Xinyi Chai; Chun Chen; Yue Liu; Yan Cao; Diya Lv; Zhanying Hong; Zhenyu Zhu; Yifeng Chai; et al. (Elsevier, 2022)
Cell membrane affinity chromatography has been widely applied in membrane protein (MP)-targeted drug screening and interaction analysis. However, in current methods, the MP sources are derived from cell lines or recombinant protein expression, which are time-consuming for cell culture or purification, and also difficult to ensure the purity and consistent orientation of MPs in the chromatographic stationary phase. In this study, a novel in situ synthesis membrane protein affinity chromatography (iSMAC) method was developed utilizing cell-free protein expression (CFE) and covalent immobilized affinity chromatography, which achieved efficient in situ synthesis and unidirectional insertion of MPs into liposomes in the stationary phase. The advantages of iSMAC are: 1) There is no need to culture cells or prepare recombinant proteins; 2) Specific and purified MPs with stable and controllable content can be obtained within 2 h; 3) MPs maintain the transmembrane structure and a consistent orientation in the chromatographic stationary phase; 4) The flexible and personalized construction of cDNAs makes it possible to analyze drug binding sites. iSMAC was successfully applied to screen PDGFRβ inhibitors from Salvia miltiorrhiza and Schisandra chinensis. Micro columns prepared by in-situ synthesis maintain satisfactory analysis activity within 72 h. Two new PDGFRβ inhibitors, salvianolic acid B and gomisin D, were screened out with KD values of 13.44 and 7.39 μmol/L, respectively. In vitro experiments confirmed that the two compounds decreased α-SMA and collagen Ӏ mRNA levels raised by TGF-β in HSC-T6 cells through regulating the phosphorylation of p38, AKT and ERK. In vivo, Sal B could also attenuate CCl4-induced liver fibrosis by downregulating PDGFRβ downstream related protein levels. The iSMAC method can be applied to other general MPs, and provides a practical approach for the rapid preparation of MP-immobilized or other biological solid-phase materials.